Anticipating Cybercrime Threats and Utilizing Digital Technology in the 2024 Simultaneous Elections - Mahmud Arif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The rapid development of digital technology must encourage the implementation of elections in Indonesia to be more efficient and effective. Funding, archiving, reporting, and socialization are aided by digital technology-based applications, which save time, money, and effort. In addition, digital technology makes it easier for people to participate and train voters. Social media and big data are also very important to disseminate information and increase election transparency and accountability. To avoid disinformation and improve political understanding, digital literacy is also needed. To increase voter participation and election quality, the 2024 simultaneous elections will use digital technology. Therefore, digital technology is expected to be an important advancement that will increase transparency, accountability, and sustainability of elections as well as increase public involvement in the democratic process. According to this study, digital technology plays an important role in the administration of elections, such as greater access to political information and social media as an effective tool for political communication. Therefore, it is hoped that the use of digital technology can increase voter participation and the level of democracy in Indonesia.